System design optimization for stand-alone photovoltaic systems sizing by using superstructure model - Azau M.A.M.; Jaafar S.; Samsudin K. (Institute of Physics Publishing, 2023)
Although the photovoltaic (PV) systems have been increasingly installed as an alternative and renewable green power generation, the initial set up cost, maintenance cost and equipment mismatch are some of the key issues that slows down the installation in small household. This paper presents the design optimization of stand-alone photovoltaic systems using superstructure model where all possible types of technology of the equipment are captured and life cycle cost analysis is formulated as a mixed integer programming (MIP). A model for investment planning of power generation and long-term decision model are developed in order to help the system engineer to build a cost effective system. Published under licence by IOP Publishing Ltd.